2004
DOI: 10.1149/1.1776592
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Oxide Precipitates in Heavily B-Doped Silicon by Infrared Spectroscopy

Abstract: Infrared absorption spectra of oxygen precipitates in boron-doped silicon with a boron concentration between 10 17 and 10 19 cm Ϫ3 are analyzed, applying the spectral function representation of composite materials. The aspect ratio of the platelet precipitates is determined by transmission electron microscopy measurements. The analysis shows that in samples with moderate doping levels (Ͻ10 18 B cm Ϫ3 ͒ SiO ␥ precipitates are formed with the same composition as in the lightly doped case. In the heavily boron-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…The BF and DF images taken under two beam condition for (004) show pronounced strain contrast making it difficult to unambiguously determine the shape of the precipitate. In contrast, the images taken under two beam condition for (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) clearly reveal that the precipitate has a plate-like character and lies on the (001) plane. From the smallest width of the contrast, the thickness of the precipitates can be roughly estimated.…”
Section: Tem Investigationsmentioning
confidence: 93%
See 1 more Smart Citation
“…The BF and DF images taken under two beam condition for (004) show pronounced strain contrast making it difficult to unambiguously determine the shape of the precipitate. In contrast, the images taken under two beam condition for (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) clearly reveal that the precipitate has a plate-like character and lies on the (001) plane. From the smallest width of the contrast, the thickness of the precipitates can be roughly estimated.…”
Section: Tem Investigationsmentioning
confidence: 93%
“…For highly boron (B) doped (pþ) material, the nucleation rate is found to be enhanced, [13][14][15][16] whereas the growth kinetics is reported to be unaffected at 1050 C. 15 The high density can be explained by several approaches like an enhancement of the density of nucleation sites in pþ material due to the presence of, e.g., B 2 O 3 complexes. 14,17 Alternatively, the O diffusivity in pþ material might even be further enhanced in the low temperature nucleation regime. [18][19][20] In addition, the surface energy and the misfit strain from the precipitates may be different in the presence of B.…”
mentioning
confidence: 99%
“…De Gryse). Combined with TEM experiments and applying an original effective medium approach to analyse the spectra, it was concluded that the precipitated phase would consist of SiO 1.17 in moderately doped and of a mixture of SiO 2 and B 2 O 3 in heavily boron doped silicon [33,34]. The model for fitting the infrared spectrum of polyhedral and plate-like oxygen precipitates could also be applied to oxygen rich germanium [35].…”
Section: Defect Spectroscopymentioning
confidence: 99%
“…10 are all the absorbance traces extracted. We focused the spectroscopic study on the 1000-1300 cm -1 spectral range, where infrared absorption bands for SiO 2 and B 2 O 3 precipitates can be detected [16]. The band around 1100 cm -1 confirms the presence of precipitates in the material from the nonideal diode AB2.…”
Section: The Trouble With Unintentional Defectsmentioning
confidence: 99%